2021
DOI: 10.1152/ajplung.00079.2021
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen dissociation curve of blood in COVID-19

Abstract: COVID-19 hinders oxygen transport to the consuming tissues by at least 2 mechanisms: In the injured lung saturation of hemoglobin is compromised, in the tissues an associated anemia reduces the volume of delivered oxygen. For the first problem increased hemoglobin oxygen affinity (left shift of the oxygen dissociation curve ODC) is of advantage, for the 2nd, however, the contrary is the case. Indeed a right shift of the ODC has been found in former studies for anemia caused by reduced cell production or hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
56
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 80 publications
1
56
1
3
Order By: Relevance
“…to the editor : In their review, “The oxygen dissociation curve of blood in COVID-19,” Böning et al ( 1 ) provide an excellent overview of the available literature, put the increased hemoglobin oxygen affinity ( 2 ) into the context of anemia, and present new, important hypotheses.…”
mentioning
confidence: 99%
“…to the editor : In their review, “The oxygen dissociation curve of blood in COVID-19,” Böning et al ( 1 ) provide an excellent overview of the available literature, put the increased hemoglobin oxygen affinity ( 2 ) into the context of anemia, and present new, important hypotheses.…”
mentioning
confidence: 99%
“…As the patients of Dr. Vogel were severely anemic, one would in fact even expect a right shift of the ODC due to an adaptive increase in the concentration of 2,3-bisphosphoglycerate ([2,3-BPG]). Anemia, a frequent complication in SARS-CoV-2 infection, usually causes an increase in [2, in most cases except those with acidosis (reviewed in our article). Astonishingly, we could detect only one publication where 2,3-BPG had been measured in patients with COVID-19 (6).…”
mentioning
confidence: 76%
“…Since it was previously reported that methemoglobin (MetHb) formation may cause a left shift of the ODC ( 4 , 5 ), we had contacted Dr. Vogel in January 2021 regarding respective measurements in his patients and learned that these data at that time had not been evaluated yet. In our article finally submitted on April 26, 2021, we thus proposed increased levels of MetHb as a potential cause of the ODC left shift in COVID-19 ( 2 ). Dr. Vogel’s letter to the editor ( 1 ) now clarifies, however, that MetHb is not the underlying cause for the observed effect in the study by Vogel et al ( 3 ).…”
mentioning
confidence: 93%
See 2 more Smart Citations